A Gene Trap Knockout of the Abundant Sperm Tail Protein, Outer Dense Fiber 2, Results in Preimplantation Lethality - Salmon, Nicholas A. (2006)
Outer dense fiber 2 (Odf2) is highly expressed in the testis where it encodes a major component of the outer dense fibers of the sperm flagellum. Furthermore, ODF2 protein has recently been identified as a wide-spread centrosomal protein. While the expression of Odf2 highlighted a potential role for this gene in male germ cell development and centrosome function, the in vivo function of Odf2 was not known. We have generated Odf2 knockout mice using an Odf2 gene trapped embryonic stem cell (ESC) line. Insertion of a gene trap vector into exon 9 resulted in a gene that encodes a severely truncated protein lacking a large portion of its predicted coil forming domains as well as both leucine zipper motifs that are required for protein–protein interactions with ODF1, another major component of the outer dense fibers. Although wild-type and heterozygous mice were recovered, no mice homozygous for the Odf2 gene trap insertion were recovered in an extended breeding program. Furthermore, no homozygous embryos were found at the blastocyst stage of embryonic development, implying a critical pre-implantation role for Odf2. We show that Odf2 is expressed widely in adults and is also expressed in the blastocyst stage of preimplantation development. These findings are in contrast with early studies reporting Odf2 expression as testis specific and suggest that embryonic Odf2 expression plays a critical role during preimplantation development in mice.